Tentativas de suicídio na adolescência: narrativas de uma dor invisível - Lourenco, Estela Ramires [UNIFESP] (2020)
Introduction: suicide is a serious public health problem, not only in Brazil, but also throughout the world. The incidence of suicides among adolescents has attracted the attention of parents, educators, paediatricians, hebiatric doctors and especially of mental health professionals, such as psychologists and psychiatrists. Objectives: to understand the possible meanings in the face of experiences of suicide attempts in the adolescent public, taking as a starting point the narratives produced by the Oral Life History Methodology. Methodological Route: A qualitative study was conducted, with the collaboration of seven adolescents aged between thirteen and eighteen years who had attempted suicide and were attended in a Non-Governmental Organization in the municipality of São José dos Campos - SP. Results: from the reading of the narratives, three central theme categories emerged: Family Relationships as a primary space of support and protection; School as a space of learning, socialization and interaction and Social Relationships and Friendship. These theme categories were interpreted by means of the Borkan's immersion-crystallization approach. The interpretations were performed with the technical contribution of anthropology and sociology, through the writings of the author David Le Breton. The results indicated that all the situations experienced and narrated by the collaborators, such as: problems with parents; mental disorder; spirituality/religiosity; lack of support; ullying; self-harming behaviour; isolation/exclusion/lack of friends; information and communication technologies (ICTs) and lack of meaning, had important repercussions. Some factors, may favour situations that lead to suicidal ideation and/or suicide attempts in adolescence, others may configure as protective factors or equally, as risk factors for suicide. Mental health promotion actions in adolescence are important and necessary strategies for the prevention of suicidal behaviour. Final Considerations: We highlight the need for collective constructions that offer care, information and guidance.